Formal synthesis of (-) anisomycin via organocatalysis - Chouthaiwale, Pandurang V.; Kotkar, Shriram P.; Sudalai, Arumugam (Arkivoc, 2009)
An efficient formal synthesis of (-) anisomycin (1), a potent antibiotic agent, has been achieved in good yields and excellent diastereoselectivity. The key steps are proline-catalyzed sequential alpha-amination or alpha-aminoxylation of aldehyde 2 followed by tandem Horner-Wadsworth-Emmons olefination.
Keywords: alpha-Amination; alpha-aminoxylation; anisomycin; olefination; Proline

Organocatalytic enantioselective approach to the synthesis of verbalactone and (R)-massoialactone - Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2011)
The organocatalytic enantioselective synthesis of verbalactone and (R)-massoialactone is described. The requisite stereogenic centers of the target molecules were constructed using L-proline-catalyzed alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination. Yamaguchi macrolactonization and ring-closing metathesis were employed as key steps in the syntheses.
Keywords: alpha-aminoxylation; Horner-Wadsworth-Emmons olefination; L-proline; massoialactone; Ring-closing metathesis; verbalactone; Yamaguchi macrolactonization

Concise formal synthesis of (-)-(6R,11R,14R)-colletallol via D-proline catalysed alpha-aminooxylation-Wittig olefination strategy - Dey, Soumen; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient enantioselective formal synthesis of marine macrolide (-)-(6R,11R,14R)-colletallol has been achieved starting from commercially available raw materials. The key reactions include the D-proline catalyzed a-aminooxylation of aldehyde followed by Horner-Wardsworth-Emmons olefination in a sequential fashion to give the macrolide key intermediate 5 in high enantiomeric purity (97% ee) and high overall yield (32%).
Keywords: alpha-aminoxylation; Asymmetric synthesis; Enantioselectivity; Natural products; organocatalysis

Proline catalyzed sequential alpha-amination/ Prins/ Ritter amidation of aldehydes: new method of construction of tetrahydropyran units - Ahuja, Brijbhushan; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient ``one-pot'' synthetic method toward highly substituted tetrahydrofuran (THP) units is reported. The key transformation involves an atom-efficient sequential proline catalyzed alpha-amination of aldehydes to give alpha-aminated aldehydes in situ and the subsequent cyclomerization with homoallylic alcohols under Prins/Ritter conditions. Notably, this method provides access to enantiopure 1,2-syn and 1,4-anti diamino alcohols via reductive ring opening of THP units.
Keywords: alpha-aminoxylation; organocatalysis; Proline catalyzed; sequential; tetrahydropyran unit